The influences of intrinsic motivation, transformational leadership, and digital skills on the intention to use digital technologies of Vietnamese banks’ employees via perceived usefulness and perceived ease of use - Trang, Pham Thu (Edelweiss Applied Science and Technology, 2024)
This study aims to investigate how intrinsic motivation, transformational leadership, and digital skills influence employees' intention to use digital technologies in Vietnamese banks through perceived usefulness and perceived ease of use. A survey involving 432 employees across 21 Vietnamese banks was conducted, and data analysis utilized PLS-SEM via SMART PLS 4.0. The findings demonstrate positive relationships between perceived ease of use, perceived usefulness, and intention to use digital technologies. Furthermore, intrinsic motivation, transformational leadership, and digital skills have a positive impact on perceived ease of use, whereas intrinsic motivation and transformational leadership have a positive influence on perceived usefulness. These results offer practical insights for Vietnamese banks to enhance digital technology adoption.